2009
DOI: 10.1002/adfm.200900843
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic States of Fluorapatite–Gelatine Nanocomposites and Their Intrinsic Electric‐Field‐Driven Morphogenesis: The Missing Link on the Way from Atomistic Simulations to Pattern Formation on the Mesoscale

Abstract: The shape development of fluorapatite (FAP)–gelatine nanocomposites is revealed by means of HRTEM investigations starting from molecular dimensions up to the formation of mesoscaled (elongated) hexagonal prisms. The composite nature of the aggregates is proved by IR spectroscopy and by chemical analyses on all states of shape development. The initial states are characterized by triple‐helical fiber protein bundles, which are mineralized step‐by‐step forming and fixing nanoplatelets of FAP in a mosaic arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Here, biomimetic materials provide an interesting approach to study such self-assembly principles by excluding complex cell activities.The biomimetic fluoraptite/gelatin composite shows both compositional and structural similarities to natural hard tissues. [1][2][3][4][5] We are interested to investigate particularly the polar state of the composite, because the formation of a polar material requires a mechanism of growth relying on a process of molecular recognition. It is known that the collagen framework of natural tissues as found in bone, dentin or tendon show a macroscopic polarization.…”
Section: Inroductionmentioning
confidence: 99%
“…Here, biomimetic materials provide an interesting approach to study such self-assembly principles by excluding complex cell activities.The biomimetic fluoraptite/gelatin composite shows both compositional and structural similarities to natural hard tissues. [1][2][3][4][5] We are interested to investigate particularly the polar state of the composite, because the formation of a polar material requires a mechanism of growth relying on a process of molecular recognition. It is known that the collagen framework of natural tissues as found in bone, dentin or tendon show a macroscopic polarization.…”
Section: Inroductionmentioning
confidence: 99%
“…For example, crystals of CaCO 3 [18][19][20][21][22][23][24], ZnO [25][26][27][28], and fluorapatite [29,30] have been grown in gel matrices or in the presence of polymers such as gelatin, chitosan, gum arabic and agarose. During the preparation process, these structure directing agents may play the role of a template and a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…The real challenge for deeper understanding of the nucleation and shape development of a biomineral (or a biomimetic material) is to clarify the structural relations between the inorganic and the organic components from the atomic level to the meso/macro-scale. This strategy was successfully followed in recent investigations on fluorapatitegelatine composites, and it was shown that even perfectly developed hexagonal prismatic individuals (the Bragg diffraction pattern corresponds to a single crystal) are not just "simple" single crystals, but actually represent a nano-composite superstructure with an additionally integrated (mesoscopic) hierarchy of gelatine microfibrils [22,23].…”
Section: Introductionmentioning
confidence: 96%